E-banking and emerging multidisciplinary processes : social, economical and organizational models - Sarlak, Mohammad Ali, 1970-; Hastiani, Asghar Abolhasani, 1966- (Hershey, PA : Business Science Reference, 2011)
'This book advances the knowledge and practice of all facets of electronic banking and develops a comprehensive framework of e-banking by taking a multidisciplinary approach to understanding its implications on traditional banks, businesses and economies'--Provided by publisher.
Includes bibliographical references (p. 184-203) and index.
Keywords: Internet banking; Banks and banking -- Automation